Effects of Learning with Ethnoscience Context on Learning Outcomes in Cognitive Aspects of Prospective Physics Teacher Students - Hikmawati Hikmawati; Sutrio; Wahyudi; Khaerus Syahidi (Jurnal Penelitian Pendidikan IPA, 2022)
Student learning outcomes in the cognitive aspect need attention because it is the professional competence of prospective teachers related to mastery of learning materials. The purpose of this study was to analyze the effects of learning in the context of ethnoscience on learning outcomes in the cognitive aspects of prospective physics teacher students. The research method used is quantitative with two stages. First, a limited trial study with a one-group pretest-posttest design at Hamzanwadi University with a total of 9 students. Second, experimental research with a post-test only group design was conducted at the University of Mataram, with a total of 77 students. In a limited trial study, an N-gain test analysis was carried out to determine the success rate of treatment with the minimum category being in the "medium" criteria. In experimental research, the effect of treatment was tested. The research sample includes all students who take the High School Physics Studies course at the Physics Education Study Program, University of Mataram, in the 2021/2022 Academic Year. The class is divided into 3 groups consisting of a class that uses an LMS with an ethnoscience context (Group A) totaling 27 people, a class using an LMS with a module (Group B) totaling 23 people, and a class using an LMS with PowerPoint (Group C) totaling 27 people. Cognitive learning outcomes data were obtained from giving essay tests after treatment. Analysis of the data used to test the hypothesis is a one-way ANOVA with SPSS 25 calculation. The results show that the average value of Group A is 78.00, Group B is 70.70, and Group C is 70.96. Lectures in Group A have a significant influence on student cognitive learning outcomes. The conclusion of this study is that learning in the context of ethnoscience has a positive effect on the professional competence of prospective physics teachers